MULTIFACTORIAL EMPIRICAL MODELS OF STANDARDS RELATIVE TORQUE COMPONENT ON THE BIT - Moisyshyn, V. M.; Zhovniruk, R. A.; Vozniy, I. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2021)
In order to establish a multifactorial empirical model standard of the relative component of the torque on the bit by the method of rational planning experimental studies were conducted at the stand of Ivano-Frankivsk National Technical University of Oil and Gas. According to this method combination of variable factors which include the axial static load FCT, the bit speed n, the stiffness C and the damping factor β of the drilling tool occurs only once. The standard is given by the product of individual dependences on variable factors. The constant factors during the planned experiment were the type and diameter of the three-cone bit and the flow rate of the washing liquid (water). The planned factorial experiment was conducted in Vorotyshche sandstone. According to its results equation of multifactor empirical models of the standard of the relative component of the torque on the bit for layers with a hardness of 1440 MPa and 2050 MPa is obtained.